UWE BoxED: empowering students in the 'real world' – providing responsible research and innovation opportunities through the BoxED project. Issue 1 (1st January 2018) - Bourne, Katherine; Wilkinson, Clare; Bancroft, Mandy; Robinson, Gareth; Noel, Catherine; Varadi, Aniko; Watson, Melanie; Foster, Maxine; Lewis, Debbie
Abstract: The Faculty of Health and Applied Sciences at the University of the West of England, Bristol has been piloting a schools outreach project entitled BoxED ( ED ucation in a Box ) since 2015. School activities are inspired from the research and teaching of our academics, and the BoxED team have developed a series of hour long activities, linked to the national curriculum, which are delivered in schools across the south-west region. Alongside the somewhat obvious benefits to school pupils, this project presents numerous opportunities and benefits for our students to develop 'real-world' skills, enabling them to successfully enter the employment market on graduating from their studies. The challenge now is to ensure the success can be built upon by securing future funding to enable a greater number of students the opportunity to engage with the project and they themselves to then develop those necessary enterprise and entrepreneurial skills appropriately, alongside their chosen subject of study – ready for the 'real-world'.